THE ROLE OF CHRISTIANITY AND CATHOLICISM IN SIGRID UNDSET'S SCANDINAVIA AND HER NOVEL KRISTIN LAVRANSDATTER - Schaff, Olivia (Literature and theology, 2001)
This article will outline the role religion plays on Sigrid Undset's trilogy Kristin Lavransdatter, as well in Scandinavia during the writing of the novel. Religion, as well as the themes of personal responsibility and growth, played an important role in Sigrid Undset's life, and her belief made itself felt in her writing. It is in fact during the writing of Kristin Lavransdatter that Catholicism began playing an increasingly vital role in Undset's life, eventually leading to her conversion to the Catholic faith in 1924. Undset believed that only by following God's law would one find true fulfilment and peace. It is when one follows his/her own path, rather than the path of God, that one encounters pain and grief. Kristin, because of her selfish pride and her inability to recognise her own sins, is incapable of growing as an individual It is only when she understands and accepts her faults that she is at last able to come to peace with herself. This article will then demonstrate Undset's desire to illustrate her belief in Catholic religious theory within the pages of her novel, as well as portraying, with vivid and realistic detail, life in fourteenth century Norway.